Allopathic Effect of Avena fatua L. and Cyperus rotundus L with Two Types of Barley (L. Hordeum Vulgare) - Eman Al-Rawi (College of Education for Pure Sciences, 2008)
Abstract This research was carried out to study the effect of aqueous extracts of the residues of two weeds Avena fatua L. and Cyperus rotundus L. on seed germination and growth of two barley cultivars(Aswad Mahaly, Arevat). Laboratory experiments were conducted to investigate the effect of aqueous extracts of residues and soils collected from under neath the weeds on seed germination, plumule and radicle length and their dry weights . Green house experiments were conducted to study the effect of aqueous extracts on germination and growth of both barley cultivars. Results of the laboratory experiments showed that the aqueous extracts of Avena fatua L. residues caused reduction in seed germination and growth while the aqueous extracts of Cyperus residues L. increasing growth, plumule length and dry weight but caused a little reduction in the radical length and its dry weight in comparison with the control.